Ameliorating Local Impacts with Architectural Research: Subprime Mortgages & Housing Quality - Dearborn, Lynne M. (Enquiry The ARCC Journal for Architectural Research, 2009)
Shock waves from the current housing crisis that still echo through Wall Street's largest financial firms, not only have threatened to topple financial markets and drive the country into a depression, but have also undermined the all-time high home ownership rate in the United States. The most attention-grabbing dimensions and headlines of the current crisis seem to be the staggering losses incurred by the likes of Bear Sterns and Citigroup, and the demise of some of the large corporations such as Washington Mutual. However, the real crisis is not on Wall Street or in the banking sector, but in low- and moderate-income and minority homes and neighborhoods throughout the country. At least ten years before the present subprime foreclosure crisis became mainstream news, these marginalized communities were feeling the negative effects of mortgage fraud and predatory lending practices occurring with regularity in the subprime market. This paper discusses an ongoing study of Subprime Lending, Mortgage Fraud and Housing Quality in process since 2002. This four-part study has employed foreclosure data with statistical and mapping analysis, detailed interviews with victims of predatory lending, systematic documentation of the resulting housing environments, and documentation of property improvements in light of victims' legal settlements. While subprime lending has supported the expansion of homeownership in the United States, this on-going study suggests that this expansion has sometimes been at the expense of safe, code-compliant living environments forlow-income, minority and elderly homeowners. Some of the victims of predatory lending and mortgage fraud have sought legal redress through the courts but many have suffered personal financial, health, emotional, and family crises as well. The current broad-scale discussion of the topic has given attention to the lack of regulation facilitating these unethical practices, but it is unclear that current discussions will lead to meaningful and lasting reform.